Impact of weather types on UK ambient particulate matter concentrations. (January 2020) - Graham, Ailish M.; Pringle, Kirsty J.; Arnold, Stephen R.; Pope, Richard J.; Vieno, Massimo; Butt, Edward W.; Conibear, Luke; Stirling, Ellen L.; McQuaid, James B.
Abstract: Each year more than 29, 000 premature deaths in the UK are linked to long term-exposure to ambient particulate matter (PM) with a diameter less than 2.5 μm (PM2.5 ). Many studies have focused on the long-term impacts of exposure to PM, but short-term increases in pollution can also exacerbate health effects, leading to deaths brought forward within exposed populations. This study investigates the impact of different atmospheric circulation patterns on UK PM2.5 concentrations and the relative contribution of local and transboundary pollutants to variations in PM2.5 concentrations. Daily mean PM2.5 observations from 42 UK background sites indicate that easterly, south-easterly and southerly wind directions and anticyclonic circulation patterns enhance background concentrations of PM2.5 at all UK sites by up to 12 μg m -3 . Results from back trajectory analysis and the European Monitoring and Evaluation Programme for UK model (EMEP4UK) show this is due to the transboundary transport of pollutants from continental Europe. While back trajectories indicate under easterly, south-easterly and southerly flow 25–50% of the total accumulated primary PM2.5 emissions originate outside of the UK, with a very polluted footprint (0.25–0.35 μg m -2 ). Anticyclonic conditions, which occur frequently (21%), also lead to increases in PM2.5 concentrations (UK multi-annual mean 14.7 μg m -3 ). EMEP4UK results indicate this is likely due the build-up of local emissions due to slack winds. Under westerly and north-westerly flow 15–30% of the total accumulated primary PM2.5 emissions originate outside of the UK, and are much less polluted (0.1 μg m -2 ) with model results indicating transport of clean maritime air masses from the Atlantic. Results indicate that both wind-direction and stability under anticyclonic conditions are important in controlling ambient PM2.5 concentrations across the UK. There is also a strong dependence of high PM2.5 Daily Air Quality Index (DAQI) values on easterly, south-easterly and southerly wind-directions, with >70% of occurrences of observed 48–71+ μg m -3 concentrations occurring under these wind directions. While north-westerly and cyclonic conditions reduce PM2.5 concentrations at all sites by up to 8 μg m -3 . PM2.5 DAQI values are also lowest under these conditions, with >80% of 0–11 μg m -3 concentrations and >50% of 12–23 μg m -3 concentrations observed during westerly, north-westerly and northerly wind directions. Indicating that these conditions are likely to be associated with a reduction in the potential health effects from exposure to ambient levels of PM2.5 . Highlights: Easterly, south-easterly and southerly winds increase ambient PM2.5 across the UK. Increased PM2.5 is due to long-range transport of PM2.5 from continental Europe. Anticyclonic conditions also increase PM2.5 due to low wind-speeds. This leads to the build-up of pollutants from local emissions. Both long-range transport and local emissions are important in controlling UK PM2.5 .